2015
DOI: 10.3390/molecules20023067
|View full text |Cite
|
Sign up to set email alerts
|

Novel Orally Active Analgesic and Anti-Inflammatory Cyclohexyl-N-Acylhydrazone Derivatives

Abstract: The N-acylhydrazone (NAH) moiety is considered a privileged structure, being present in many compounds with diverse pharmacological activities. Among the activities attributed to NAH derivatives anti-inflammatory and analgesic ones are recurrent. As part of a research program aiming at the design of new analgesic and anti-inflammatory lead-candidates, a series of cyclohexyl-N-acylhydrazones 10–26 were structurally designed from molecular modification on the prototype LASSBio-294, representing a new class of cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 39 publications
3
26
0
Order By: Relevance
“…The assignment of the possible geometrical isomer obtained (ie, Z or E ) was performed considering the chemical shift of the imine hydrogen and based on previous data from literature. 13 17 These data indicated that compounds 4–9 were obtained as E -diastereoisomers (N=CH in configuration E).…”
Section: Resultsmentioning
confidence: 91%
“…The assignment of the possible geometrical isomer obtained (ie, Z or E ) was performed considering the chemical shift of the imine hydrogen and based on previous data from literature. 13 17 These data indicated that compounds 4–9 were obtained as E -diastereoisomers (N=CH in configuration E).…”
Section: Resultsmentioning
confidence: 91%
“…Inspired by a report that 2 itself inhibits TRPV6, 23 , 24 we finally prepared a series of capsaicin analogues reproducing the essential pharmacophoric features of the natural product (a methyl-catechol and a hydrophobic tail connected via an amide bond linker) by connecting vanillin with aliphatic chains via a sulfonylhydrazone ( 41 and 42 ), 25 N -acyl hydrazone ( 43 and 44 ) 26 or sulfonylglycine hydrazone ( 45 and 46 ) 27 , 28 as an amide replacement. 29 , 30…”
Section: Resultsmentioning
confidence: 99%
“…Literature reports for N -acyl- and N -aroylhydrazones derived from aryl- and heteroaryl aldehydes indicate that these compounds may exist both in DMSO- d 6 solution [ 39 , 40 , 41 , 42 ] and solid phase [ 43 , 44 , 45 , 46 ] in the form of E -geometrical isomers. Other studies revealed the presence of the mixtures of two forms: cis and trans amide conformers of N -acyl- [ 39 , 40 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ] and N -aroylhydrazones [ 52 , 53 ] in solution.…”
Section: Resultsmentioning
confidence: 99%